Factors Influencing Core Brand Attitude and Consumer Perceptional Fit in the Pandemic Era and Their Implications for Purchase Intention Toward Extended Product - Arinto, Boby; Aprilio, Agauta (Conference Series, 2021)
Challenges faced by people in today's pandemic conditions are the dependence on the internet and communication tools because all the processes of work from home or school from home activities are done online. In addition to the stable and strong internet connection, the use of reliable communication equipment tools became a must and people were looking for a brand that suited this need. However, it turns out that a strong brand in the electronics industry has not guaranteed success when doing brand extension in the category of communication tools. This is experienced by Sharp, a leading electronics manufacturer from Japan.This research aims to find out whether core brand image, core brand attitude, brand association, product connection, use experience, and consumer perceptional fit, have an influence on purchase intention toward extended product in the case of Brand Sharp on its communication device product, the Sharp Aquos Zero 2 Smartphone. Quantitative research methods have been conducted using online questionnaires to respondents who are over 17 years old and know sharp electronic products, have owned their products and have seen sharp Aquos Zero 2 reviews but have never bought the product. The structural equation model (SEM) method was used to analyze these 6 research hypotheses.The result was a positive relationship between core brand image, core brand attitude, brand association, product connection, use experience, and consumer perceptional fit on purchase intention toward extended product smartphone. However, on the other hand, the core brand image and use experience variables have no influence on core brand attitude.